Serum high sensitive C-reactive protein level and its correlation with lipid profile among dyspeptic patients with or without Helicobacter pylori infection in East Gojjam zone, Ethiopia - Baye, Gelagey; Wondmneh, Bayu; Ashenef, Baye; Jemal, Mohammed; Baylie, Temesgen (Frontiers in Cardiovascular Medicine, 2024)
Introduction: Dyspepsia is a group of symptoms located in the gastroduodenal area of the upper gastrointestinal tract characterized by epigastric pain, postprandial completeness, or early satiety and occasionally related to heartburn. Helicobacter pylori is the major causative agent of dyspepsia and gastric-related disorders; besides, it alters different metabolic processes in the human body, such as lipid metabolism and inflammatory processes. Even though dyslipidemia and inflammation are independent risk factors for cardiovascular disorders, we are assessing the interaction between serum lipids and highly sensitive C reactive protein levels among dyspeptic patients to predict potential cardiovascular disorders.Objectives: To assess serum high sensitive C reactive protein levels and its correlation with lipid profile among dyspeptic patients.: A hospital-based comparative cross-sectional study was conducted from May 2022 to March 2023 in East Gojjam, Ethiopia. One hundred helicobacter pylori-positive and 100 helicobacter pylori-negative dyspeptic patients were included. Data were checked for completeness and entered into SPSS version 26.0 software and analyzed. The association between variables was determined by Pearson correlation analysis. A p-value < 0.05 was considered statistically significant.The mean serum high sensitive C reactive protein was 8.09 ± 7.84 mg/L, and serum high-density lipoprotein, low-density lipoprotein, total cholesterol, and triglyceride were (35.35 ± 7.5, 105.07 ± 87.63, 142.31 ± 71.31, 160.07 ± 43.06) mg/dL, respectively, for helicobacter pylori positive dyspeptic patients. Among these values, high-density lipoprotein is negatively correlated with high sensitive C reactive and total cholesterol is positively correlated with high sensitive C reactive levels among helicobacter pylori-infected dyspeptic patients with a p-value < 0.05, but in helicobacter pylori negative dyspeptic patients, there is no significant correlation between lipid profile and high sensitive C reactive levels.Serum high sensitive C reactive levels had a negative correlation with highdensity lipoprotein and a positive correlation with total cholesterol among Helicobacter pylori-positive dyspeptic patients. Therefore, the significant interaction between serum lipid levels and inflammation exacerbates the potential risk of cardiovascular disorders among Helicobacter pylori-positive dyspeptic patients.